Curiosity and Affect-Driven Cognitive Architecture for HRI - Berto, Leticia; Tanevska, Ana; Cirne, Azamor; Costa, Paula; Simoes, Alexandre [UNESP]; Gudwin, Ricardo; Rea, Francesco; Colombini, Esther; Sciutti, Alessandra (My University, 2025)
This study explores how humans and cognitive robots with different value systems and motivations understand each other's needs in free-form interactions. We developed a cognitive architecture that links sensing and perception to internal motivation and an intrinsic value system for determining actions. Inspired by young children's needs, this architecture includes three drives: learning, interaction, and recharging, each with varying dependence on the human partner. We aimed to assess how experimentally changing the importance of these drives within a fixed architecture affects interaction dynamics with human partners (acting as caregivers) and their understanding of the robot's needs. By adjusting the learning and interaction drives, we created two robot profiles: Playful, which prioritizes environmental exploration and playfulness to reduce boredom, and Social, which focuses on social interaction through touch and visual contact to increase comfort. Our findings show that changing the importance of these drives produces distinct behaviors and human perceptions. Robot behaviors matched their profiles, and participants adapted their responses accordingly. Participants identified and attributed distinct traits to each robot without knowing the specific profiles. Despite variability among human partners, the robots, especially the playful one, were generally well understood by most participants.
Keywords: Affective computing; cognitive architecture; human-robot interaction; intrinsic motivation; robot profiles